DEVELOPMENT OF PROJECT BASED TEACHING MATERIAL IN BUILDING CONSTRUCTION COURSE - Zulkifli Matondang; Krisda Fadila (LPPM Universitas Negeri Jakarta, 2023)
Building Construction is a compulsory subject in the Building Engineering Education Study Program which is expected in this course to have the ability to design systems and infrastructure in the civil engineering field as needed by considering various constraints such as economic, environmental, health, and security constraints. Covid-19 harms life so the world of education also wants to participate in breaking the spread of the Covid-19 virus. The subsidized houses that have been built have met the existing requirements, although they are not perfect, they can still be said to be livable houses. However, a serious problem is that after being given a lot of people added the initial building but did not meet the requirements. This development research produces project-based teaching materials products. This study uses the development of Borg and Gall with the stages of analyzing potential problems, data collection, product design, design validation, design revision, product testing, revision, and reporting. The teaching materials developed contain the characteristics and designs of disaster response houses adapted to the Building Construction course material and are project in nature. The results of the study obtained that the teaching materials developed were suitable for use as teaching materials in the process of learning activities based on the overall average score of the material expert aspect of 3.6 and the media expert 3.6 very good category